Electrochemical thermal modeling and experimental measurements of 18650 cylindrical lithium-ion battery during discharge cycle for an EV. (5th May 2018) - Panchal, S.; Mathew, M.; Fraser, R.; Fowler, M.
Highlights: Designed and developed the battery thermal testing system. Developed ECT model using ANSYS Fluent. Studied the temperature and voltage profile at different discharge rates. Validated the model with the experimental data. Abstract: Study of thermal performance in lithium-ion battery cell is crucial which directly affects the safety. Even though the operation of a lithium-ion battery cell is transient phenomena in most cases, most available thermal models for lithium-ion battery cell predicts only steady-state temperature fields. This paper presents a mathematical model to predict the transient temperature and voltage distributions of 18650 cylindrical lithium-ion battery at different discharge rates. For this, the 18650 cylindrical lithium-ion battery cell is tested inside the lab with an air-cooling method by four thermocouples mounted on the battery surface under four constant current discharge rates of 1 C, 2 C, 3 C, and 4 C in order to provide quantitative data regarding thermal behavior of lithium-ion batteries. Later, the numerical model is developed using ANSYS CFD software and it is found that the model predictions are in good agreement with experimental data for temperature and voltage profiles. The highest temperature is 46.86 °C at 4 C discharge rate as obtained from simulation. The results also show that the increased C-rates results in increased temperature on the principle surface of the battery.